Effects of Nanoparticle Shape on Slot-Jet Impingement Cooling of a Corrugated Surface With Nanofluids - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Asme, 2017)
Numerical study of jet impingement cooling of a corrugated surface with water-SiO2 nanofluid of different nanoparticle shapes was performed. The bottom wall is corrugated and kept at constant surface temperature, while the jet emerges from a rectangular slot with cold uniform temperature. The finite volume method is utilized to solve the governing equations. The effects of Reynolds number (between 100 and 500), corrugation amplitude (between 0 and 0.3), corrugation frequency (between 0 and 20), nanoparticle volume fraction (between 0 and 0.04), and nanoparticle shapes (spherical, blade, brick, and cylindrical) on the fluid flow and heat transfer characteristics were studied. Stagnation point and average Nusselt number enhance with Reynolds number and solid particle volume fraction for both flat and corrugated surface configurations. An optimal value for the corrugation amplitude and frequency was found to maximize the average heat transfer at the highest value of Reynolds number. Among various nanoparticle shapes, cylindrical ones perform the best heat transfer characteristics in terms of stagnation and average Nusselt number values. At the highest solid volume concentration of the nanoparticles, heat transfer values are higher for a corrugated surface when compared to a flat surface case.
Keywords: Backward-Facing Step; Heat-Transfer; Thermal-Conductivity; Rotating Cylinder; Mixed Convection; Natural-Convection; Magnetic-Field; Impinging Jet; Circular Jet; Flow